Analisis Nama Produk dalam Makanan Ringan Jepang di OH!SOME Store: Kajian Lanskap Linguistik: An Analysis of Japanese Snack Product Naming at Oh!Some Store: Linguistic Landscape Perspective - Sony Difa Febrianda; Sri Aju Indrowaty (Jurnal Pendidikan Bahasa Jepang Undiksha, 2026)
Product identity plays an important role in a trademark, serving as a tool or intermediary between a company and its consumers. A product name is expected to create a strong perception of the advantages or benefits of the product it offers, as well as to differentiate it from similar or comparable products. This study aims to determine the function of information on snack foods sold at OH!SOME. This study employs a qualitative descriptive method grounded in the theoretical framework of linguistic landscape theory. The findings reveal that the information contained in the names of Japanese snack foods is based on the texture, taste, and primary ingredients of the snacks. Additionally, the analysis examines Japanese snack products that utilize Japanese characters such as hiragana, katakana, romaji, and kanji.